2020
DOI: 10.1177/0300060520943453
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of irbesartan and benazepril against vaginal vascular remodeling and fibrosis in female spontaneously hypertensive rats

Abstract: Objective To compare the potential beneficial effects of the angiotensin converting enzyme inhibitor (ACEI) benazepril and the angiotensin II receptor 1 blocker (ARB) irbesartan on vaginal vascular remodeling and fibrosis in female spontaneously hypertensive rats (SHRs). Methods Twelve-week-old female SHRs were treated with irbesartan or benazepril for 12 weeks. Vaginal renin angiotensin system (RAS) components were detected by polymerase chain reaction and western blot and vaginal α-smooth muscle actin (α-SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…[71][72][73] Previous studies have shown that abundant a-SMA was found in a rat model of hypertension, including in the heart, 74,75 kidney, 76 and genitals. [77][78][79][80] Consistently, we showed that female SHRs had significantly increased levels of a-SMA in their clitoral and vaginal tissue. Collectively, we proved that hypertension damages female sexual function and increases the levels of a-SMA and collagen deposition (ie, Col-I and Col-III).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…[71][72][73] Previous studies have shown that abundant a-SMA was found in a rat model of hypertension, including in the heart, 74,75 kidney, 76 and genitals. [77][78][79][80] Consistently, we showed that female SHRs had significantly increased levels of a-SMA in their clitoral and vaginal tissue. Collectively, we proved that hypertension damages female sexual function and increases the levels of a-SMA and collagen deposition (ie, Col-I and Col-III).…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies showed that ARBs had the favorable effects on sexual function. 10,13,77,80 The previous clinical study showed that VAL treatment improved sexual function in hypertensive females: the perception of some dimensions of libido, including sexual desire and sexual relations. 13 Some animal experiments also confirmed that RAAS inhibition reversed hypertension-induced alterations in female genital structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC analysis was performed as previously described [28]. Briefly, paraffin sections were deparaffinized, rehydrated, antigen recovered, and incubated overnight at 4˚C in the presence of the following primary antibodies: anti-α-SMA (1:1000, ab124964, Abcam); anti-COL1A1 (1:100,ab34710, Abcam); anti-TGF-β (1:50, SC-130348, Santa Cruz Biotechnology); anti-TGFβ R1 (1:75, ab31013, Abcam) and anti-TGF-β R2 (1:50, ab61213, Abcam).…”
Section: Histopathological and Immunohistochemical Analysismentioning
confidence: 99%